Extracellular vesicles as biomarkers and modulators of atherosclerosis pathogenesis - Patel, Sarvatit; Guo, Mandy Kunze; Abdul Samad, Majed; Howe, Kathryn L. (Frontiers in Cardiovascular Medicine, 2023)
Extracellular vesicles (EVs) are small, lipid bilayer-enclosed structures released by various cell types that play a critical role in intercellular communication. In atherosclerosis, EVs have been implicated in multiple pathophysiological processes, including endothelial dysfunction, inflammation, and thrombosis. This review provides an up-to-date overview of our current understanding of the roles of EVs in atherosclerosis, emphasizing their potential as diagnostic biomarkers and their roles in disease pathogenesis. We discuss the different types of EVs involved in atherosclerosis, the diverse cargoes they carry, their mechanisms of action, and the various methods employed for their isolation and analysis. Moreover, we underscore the importance of using relevant animal models and human samples to elucidate the role of EVs in disease pathogenesis. Overall, this review consolidates our current knowledge of EVs in atherosclerosis and highlights their potential as promising targets for disease diagnosis and therapy.